Mobile solid waste ıncineration project for the case study of Şırnak - trash, animal and agricultural waste-mobile co-ıncineration - Tosun, Yıldırım İsmail (Giresun Üniversitesi, 2016)
Evaluation of Bio-waste for Sirnak Province in the context of solid waste management and aimed to create a mobile solid waste incineration system. In some plants burning solid waste management practices based on gasification and pyrolysis process it can be operated as interdependent as mobile or integrated. The implementation of bio-waste collection and waste separation methods the amount of solid waste to be recycled or composted will affect the amount produced. In Sirnak that approximately 120 thousand tons of solid waste generated and neighboring Siirt and Hakkari projecting a mobile mind similar waste incinerators in the province were studied in this work. Thus, waste and biomass waste streams that can be done in the conscious of the waste classification of the area, alongside environmental impact, recycling waste, such as energy recovery benefits will be provided. Mobile solid waste management, recycling, composting or waste of energy technologies are included. In this case, the classified as waste products should be investigated and should also be aware of the processing, depending on the market of products obtained from these requirements. Mobile waste management, design, integration and demonstrate flexibility in terms of existing business and to reach the village social, it is necessary to adapt the best economic and environmental conditions. This type of solid waste management including waste incineration and mobile units / economic and environmental conditions in the integrated system provides the flexibility to change waste diverted to other treatment systems.
Keywords: Mobile İncineration; Co-Incineration; Biomass; Agricultural Waste Combustion